Donald Trump as a Critical-Thinking Teaching Assistant - Sullivan, Stephen (Informal Logic, 2018)
Donald Trump has been a godsend for those of us who teach critical thinking. For he is a fount of manipulative rhetoric, glaring fallacies, conspiracy theories, fake news, and bullshit. In this paper I draw on my own recent teaching experience in order to discuss both the usefulness and the limits of using Trump examples in teaching critical thinking. In Section One I give the framework of the course; in Section Two I indicate Trump’s relevance to many important concepts in the course; and in Section Three I argue that critical thinking instructors should restrain themselves from overreliance on Trump-examples.